Optimizing bowel preparation for colonoscopy: A cross-sectional study of the Chinese population - Luo, Li; Liu, Yuan; Zhang, Lingling; Lai, Yihuan; Li, Yansheng; Liu, Kejia; Gong, Houwu; Jiang, Dapeng; Wang, Erchuan (Frontiers in Public Health, 2022)
Background: The quality of bowel preparation is an important factor in the success of colonoscopy. However, the quality of bowel preparation is often affected by multiple factors. The main objective of this study was to explore the specific factors that affect the quality of bowel preparation. Methods: Patients were consecutively recruited from the gastroenterology department in Union Hospital, Tongji Medical College, Huazhong University of Science and Technology in Wuhan from May 2018 to December 2018. All patients were undergoing colonoscopy. Bowel preparation was evaluated by the Ottawa Bowel preparation Scale (OBPS) and all patients were categorized into 2 groups according to the OBPS. Multivariate analysis was conducted to identify the factors associated with the bowel preparation quality. Results: A total of 910 patients were included in the analysis with an average age of 48.62 ± 13.57 years. Patient source (P <0.001) and preparation method (P = 0.029) were correlated with OBPS adequacy. In addition, after stratified by age, preparation method (P=0.022) was a significant factor among patients under 50 years old; whereas waiting time (P=0.005) was a significant factor among patients over 50 years old. Conclusion: Bowel preparation should be tailored based on the age of the patients to determine the most appropriate plan, including the most appropriate waiting time and the most appropriate purgative combination. Doctors should also focus more on the quality of bowel preparation in inpatients, who are more likely than outpatients to have inadequate bowel preparation